2014
DOI: 10.1021/es4049384
|View full text |Cite
|
Sign up to set email alerts
|

A PARAFAC-Based Long-Term Assessment of DOM in a Multi-Coagulant Drinking Water Treatment Scheme

Abstract: A parallel factor (PARAFAC) analysis approach was used to study the character and composition of dissolved organic matter (DOM) in a multicoagulant (two aluminum-based coagulants) full scale drinking water treatment plant. A three year, long-term assessment was conducted based on deconstruction of the excitation-emission matrices (EEM) of over 1000 water samples collected before and after parallel coagulation treatment basins. Two humic moieties and a protein-like group were identified in the raw and treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 45 publications
(116 reference statements)
4
23
0
Order By: Relevance
“…Coagulation of the raw water sample has been found to have little effect on the signature of the fluorophores but rather, decreases the fluorophore intensity which correlates to a decrease in DOC of the water [47]. The two different coagulants in this study exhibited different preferential removal of DOC.…”
Section: Fluorescence and Doc Analysismentioning
confidence: 62%
See 1 more Smart Citation
“…Coagulation of the raw water sample has been found to have little effect on the signature of the fluorophores but rather, decreases the fluorophore intensity which correlates to a decrease in DOC of the water [47]. The two different coagulants in this study exhibited different preferential removal of DOC.…”
Section: Fluorescence and Doc Analysismentioning
confidence: 62%
“…for Alum and ACH, respectively. Studies have shown that fluorescence components that correlate to THM formation are humic-like components C1 and C2, while HAA formation correlates with humic-like components and microbial-derived component (C3) [17,47]. PARAFAC component scores, which have been shown to correlate with THM formation, were 10%-20% higher in ACH treated water than water treated with Alum.…”
Section: Fluorescence and Doc Analysismentioning
confidence: 99%
“…Here the organic substances are characterized by excitation-emission matrices that are analyzed by multi-way techniques, in particular parallel factor analysis (PARAFAC) [31,32]. By evaluating data from a full-scale drinking water treatment plant, Sanchez et al [33] have demonstrated that this approach was suitable to evaluate the performance of two coagulants. Shutova et al [10] identified a number of fluorescence parameters that were useful to characterize the properties of organic substances with respect to treatability.…”
Section: Feed-forward Control Based On Raw Water Qualitymentioning
confidence: 99%
“…EEM-PARAFAC is very useful in tracing different sources/compositions of DOM. For example, Sanchez et al (2014) reported using EEM-PARAFAC that humic-like substances were preferentially removed from a bulk DOM by aluminum-based coagulation processes. Meanwhile, it was reported that protein-like fluorescent components were more effectively eliminated by membrane filtration than humic-like components (Shutova et al, 2014).…”
Section: Introductionmentioning
confidence: 99%